The migration-security nexus: desecuritization and the shift towards the sustainable approach - Paulina Polko (Journal of Modern Science)
Objectives Migration emerged as a security issue in the context of the geopolitical dislocation shaped by the end of the Cold War and by social and political shifts associated with globalization processes. As such, the migration-security nexus tends to present the understanding of migration and migrants as a threat to the destination or transit countries. However, the increasing number of people on the move requires a change in the approach. The article aims to propose a wider and more sustainable approach to the migration-security nexus based on the desecuritization of migration processes and their participants. Using comparative analysis and discourse analysis, points to three levels of the migration-security nexus, taking into account the multiple perspectives of migration processes and their practical implications.